Literary Portrait of V.G. Shershenevich in the Works of Barnaul Writers - Tatiana A. Bogumil (Studia Litterarum)
Imaginist poet V.G. Shershenevich died and was buried in 1942 in Barnaul. The fact of the death and burial of the capital’s author in a provincial town has become a landmark event for regional self-identification, and initiated a particular thematic line in local history and fiction. For the first time the article reveals the image of V.G. Shershenevich, which was developed in the work of Barnaul writers. The analysis of poetic and prose texts shows how the reconstruction of the last days of the poet’s life fits him into the urban landscape, how the grave becomes a semantically productive element of the locus. The basic motifs that model the image of the writer are associated with the change of poles of the oppositions “center — periphery,” “glory — oblivion,” “friend — alien (foreign),” “genius – mediocrity,” “friendship — enmity” with S.A. Yesenin. Literary portrait of Shershenevich comes from the synthesis of the features of his poetics, aesthetic attitudes, life events and the realities of the city. Altai writers tend to project literary and historical facts related to the imagist onto their own work and destiny. There is a tendency to turn the poet into a genius loci.